Revaluation of zooplankton wet weight data of the NORPAC net samples collected in the Indian sector of the Southern Ocean - Yukiko Ukai; Kunio T. Takahashi; Mitsuo Fukuchi; Atsushi Tanimura (National Institute of Polar Research, 2014)
The Japanese Antarctic Research Expedition (JARE) has been conducting routine observations of zooplankton in the Indian Ocean sector of the Southern Ocean with standard NORPAC nets (mesh size: 330 μm and 100 μm) every austral summer since the 1972/73 season (JARE-14). We used a new processing method to measure the wet weight of the zooplankton only because the effect of the inclusion of phytoplankton on the wet weight has been problem in previous studies. The repeated-measurement made in this study show that 26.7 % of the total wet weight of the samples that were collected with 330 μm (targeting zooplankton) was attributable to phytoplankton. We have thus demonstrated that previous reports have overestimated the wet weight of zooplankton by approximately 30 %. Furthermore, when we compared the wet weights caught with the 330 μm and 100 μm nets, they did not differ significantly for zooplankton greater than 10 mm, whereas the wet weights of small sized zooplankton less than 10 mm caught with 100 μm nets were approximately two-fold greater than those caught with 330 μm nets.